Antimicrobial studies of titanium dioxide thin films. - Tay, Derrick Kok Sing. (2009)
Antimicrobial surfaces have extensive applications as self-cleaning surfaces, for air and water purification technologies and even for coating implants to prevent infections. The bactericidal effects of titanium dioxide (TiO2) photocatalyst in the presence of ultraviolet (UV) irradiation have been well documented and proven effective as an antimicrobial. In this work, it was found that the antimicrobial effect of TiO2 alone constituted 87% of the total photokilling effect of an UV-illuminated TiO2 surface. In addition, the biocidal effect of TiO2 was proven to be 6.5 times more effective than that of UV-A irradiation at 150 μW/cm2. Hence it was concluded that TiO2 was the major contributor of cellular death under UV irradiation and that even under weak UV irradiation the antimicrobial effects were significant. Results had also shown that TiO2 surfaces demonstrated antimicrobial effects even in the absence of contact with the cells, hence proving that cellular contact was not a prerequisite for the biocidal effects of TiO2 to occur.